ELECTRONIC USE OF JOURNALS SUBSCRIBED TO BY UINSU FOR STUDENTS OF THE FACULTY OF SOCIAL SCIENCES : Pemanfaatan Elektronik jurnal yang di langgan uinsu bagi mahasiswa fakultas ilmu sosial - Annur Rosida Harahap; Muslih Faturrahman (SOSIOEDUKASI, 2025)
This study aims to find out the use of electronic journals subscribed by uinsu for students of the faculty of social sciences. This research was conducted at the Faculty of Social Sciences UINSU Medan. The method in this study uses a qualitative method with data sources through observation, interviews and documentation with students and librarians. Based on the results of interviews with students of the Faculty of Social Sciences UINSU, it can be concluded that there are still many students who do not fully know that the campus provides access to electronic journals (e-journals). Information about this e-journal service is mostly obtained indirectly, both from lecturers and peers, and not from official socialization carried out by the campus or library. The lack of information and promotion causes many students to not know the benefits and potential of e-journals as a credible and up-to-date source of academic literature. In addition, in terms of frequency of use, the majority of students rarely use campus e-journals, even only using them when they are working on a final project or thesis. The low intensity of this utilization cannot be separated from the lack of technical understanding of students in accessing and navigating the available e-journal platforms. This is also exacerbated by the absence of regular training or guidance from libraries and faculties that can help students.